Sequence conservation of Plasmodium vivax glutamate dehydrogenase among Korean isolates and its application in seroepidemiology. (December 2017) - Seol, Bomin; Shin, Hyun-Il; Kim, Jung-Yeon; Jeon, Bo-Young; Kang, Yoon-Joong; Pak, Jhang-Ho; Kim, Tong-Soo; Lee, Hyeong-Woo
Abstract Background Glutamate dehydrogenase of malaria parasites (pGDH) is widely used in rapid diagnostic tests for malaria. Variation in thepGDH gene among Korean isolates ofPlasmodium vivax was analysed, and a recombinant pGDH protein was evaluated for use as antigens for the serodiagnosis of vivax malaria. Methods Genomic DNA was purified from blood samples of 20 patients and thepGDH gene ofP. vivax was sequenced. Recombinant protein was prepared to determine the antigenicity of pGDH by enzyme-linked immunosorbent assay (ELISA). Results Partial sequence analysis of theP. vivax pGDH gene from the 20 Korean isolates showed that an open reading frame (ORF) of 1410 nucleotides encoded a deduced protein of 470 amino acids. The amino acid and nucleotide sequences were conserved among all the Korean isolates. This ORF showed 100% homology withP. vivax strain Sal-I (GenBank accession No. XP_001616617.1). The full ORF (amino acids 39–503), excluding the region before the intron, was cloned from isolateP. vivax Bucheon 3 (KJ726751) and subcloned into the expression vector pET28b for transformation intoEscherichia coli BL21(DE3)pLysS. The expressed recombinant protein had a molecular mass of approximately 55 kDa and showed 84.8% sensitivity (39/46 cases) and 97.2% specificity (35/36 cases) in an ELISA. The efficacy of recombinant pGDH protein in seroepidemiological studies was also evaluated by ELISA using serum samples collected from 876 inhabitants of Gyodong-myeon, Ganghwa County, Incheon Metropolitan City. Of these samples, 91 (10.39%) showed a positive reaction with recombinant pGDH protein. Among the antibody-positive individuals, 13 (14.29%) had experienced malaria infection during the last 10 years. Conclusion ThepGDH genes ofP. vivax isolates from representative epidemic-prone areas of South Korea are highly conserved. Therefore, pGDH is expected to be a useful antigen in seroepidemiological studies. It was difficult to identify the foci of malaria transmission in Gyodong-myeon based on the patient distribution because of the very low parasitaemia of Korean vivax malaria. However, seroepidemiology with recombinant pGDH protein easily identified regions with the highest incidence of malaria within the study area. Therefore, recombinant pGDH protein may have a useful role in serodiagnosis.